Preoperative planning of primary total hip arthroplasty using conventional radiographs()() - Miashiro, Edson Hidenori (Rev Bras Ortop, 2014)
OBJECTIVE: the objective of this study was to present an analog method for preoperative planning of primary total hip arthroplasty procedures based on measuring the components by overlaying the transparencies of the prosthesis on the preoperative radiographs and checking the accuracy, both for predicting the size of the acetabular and femoral components used and for restoring the offset and correcting the dysmetria. METHODS: between March 2005 and July 2009, 56 primary total hip arthroplasty procedures performed on 56 patients at the Mario Covas State Hospital in Santo André were analyzed. The measurements on the femoral and acetabular components obtained through planning were compared with those that were used in the surgery. The offsets measured through the preoperative planning were compared with those measured on the postoperative radiographs. Dysmetria was evaluated before and after the operation. RESULTS: accuracy of 78.6% (p < 0.001) in predicting the size of the acetabular component and 82.2% (p < 0.001) in predicting the femoral nail was observed. The offsets measured through preoperative planning were statistically similar to the offsets measured on the postoperative radiographs. After the operation, we observed absolute equalization in 48.2% of the cases. In 87.5%, the dysmetria was less than or equal to 1 cm and in 69.6%, it was less than or equal to 0.5 cm. CONCLUSIONS: the accuracy was 78.6% and 82.2%, respectively, for the acetabular and femoral components. The offsets that were planned preoperatively were statistically similar to those measured on postoperative radiographs. We found absolute equalization in 48.2% of the cases.